Persepsi dan Makna Tradisi Bajapuik bagi Masyarakat Minang Perantauan di Pasar Minggu Jakarta Selatan - Putri Aulia; Maila D.H Rahiem; Cut Dhien Nourwahida (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
This research explores the perspectives and meanings of the Bajapuik tradition for the Minangkabau diaspora community in Pasar Minggu, South Jakarta. The study utilizes an explorative descriptive qualitative method. The researcher interviewed 2 ninik-mamak figures and 10 Minangkabau community members who have participated in the Bajapuik tradition. The research data indicates that: 1) The Minangkabau diaspora community interprets the Bajapuik tradition as a courtship tradition; 2) The importance of the involvement of ninik-mamak in leading the implementation of the Bajapuik tradition; 3) The Bajapuik tradition performed in diaspora has undergone changes in its implementation procedures; 4) The determination of the Japuik money is influenced by the social status of the man. The researcher concludes that the implementation of the Bajapuik tradition in the diaspora has experienced changes and shifts based on its original cultural values, but it is still carried out and preserved by involving traditional figures and the Minangkabau community to provide cultural understanding of the Bajapuik tradition.